2001
DOI: 10.1038/sj.bjp.0704147
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological evidence for the activation of potassium channels as the mechanism involved in the hypotensive and vasorelaxant effect of dioclein in rat small resistance arteries

Abstract: 1 The hypotensive and vasorelaxant e ect of dioclein in resistance mesenteric arteries was studied in intact animals and isolated vessels, respectively. 2 In intact animals, initial bolus administration of dioclein (2.5 mg kg 71 ) produced transient hypotension accompanied by an increase in heart rate. Subsequent doses of dioclein (5 and 10 mg kg 71 ) produced hypotensive responses with no signi®cant change in heart rate. N G -nitro-Larginine methyl ester (L-NAME) did not a ect the hypotensive response. 3 In e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…Similar effects have been shown for the isoflavone puerarin [32]. Dioclein, a flavonoid isolated from the root of Dioclea grandiflora, a legume of the native Americans, causes hypotension in normotensive rats [33]. Using preparations of isolated rat mesenteric arteries, the authors showed that the vasorelaxant effect is mainly due to hyperpolarization caused by an opening of BK Ca channels [33].…”
Section: Activation Of the Vascular Calcium Activated Potassium Channmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar effects have been shown for the isoflavone puerarin [32]. Dioclein, a flavonoid isolated from the root of Dioclea grandiflora, a legume of the native Americans, causes hypotension in normotensive rats [33]. Using preparations of isolated rat mesenteric arteries, the authors showed that the vasorelaxant effect is mainly due to hyperpolarization caused by an opening of BK Ca channels [33].…”
Section: Activation Of the Vascular Calcium Activated Potassium Channmentioning
confidence: 54%
“…Dioclein, a flavonoid isolated from the root of Dioclea grandiflora, a legume of the native Americans, causes hypotension in normotensive rats [33]. Using preparations of isolated rat mesenteric arteries, the authors showed that the vasorelaxant effect is mainly due to hyperpolarization caused by an opening of BK Ca channels [33]. Saponara et al found that the citrus flavonoid naringenin also dilates endothelium denuded rat aortic rings by activation of BK Ca channels [34].…”
Section: Activation Of the Vascular Calcium Activated Potassium Channmentioning
confidence: 99%
“…To investigate the possible mechanism(s) responsible for CLME-induced relaxation, the preparations without endothelium were pre-contracted with phenylephrine (10 M) for 30 min after being pre-incubated with one of the following inhibitors: glibenclamide (10 M), BaCl 2 (1 mM), tetraethylammonium (1 mM) or 4-aminopyridine (1 mM). The concentration used for each inhibitor of K + channels is sufficient to antagonize selectively those channels in arterial smooth muscle (Nelson and Quayle, 1995;Côrtes et al, 2001).…”
Section: Effect Of Clme On Mesenteric Rings Pre-contracted With Phenymentioning
confidence: 99%
“…In this case, the relaxation in response to exogenous NO is resistant to inhibitors of guanylate cyclase. This additional component of relaxation has been named endothelium-derived hyperpolarizing factor (EDHF) (17,22). The contribution of NO and EDHF to endotheliumdependent vasodilation varies according to the vessel studied (27).…”
Section: +mentioning
confidence: 99%
“…Superior MAs were isolated as described previously by Cortês and colleagues (17). In brief, rats were killed by exposure to CO 2 and exsanguinated.…”
Section: Rat Isolated Mamentioning
confidence: 99%